Relationships between addiction and the COMT rs4680 Gene Polymorphism: Hubungan antara kecanduan dan Polimorfisme Gen COMT rs4680 - Wael Sattar Jaber; Fulla Abd Alsattar Alriyahee (Academia Open, 2025)
General background: Addiction to drugs and alcohol presents a severe public health burden worldwide, driven by complex interactions between genetic and environmental factors. Specific background: The catechol-O-methyltransferase (COMT) gene, particularly the rs4680 (Val158Met) polymorphism, is known to influence dopamine regulation in the prefrontal cortex, a key area in addiction pathology. Knowledge gap: However, there remains limited genetic data on this polymorphism's role in addiction susceptibility within the Iraqi population. Aims: This study aimed to investigate the association between COMT rs4680 genotypes and the risk of drug and alcohol addiction among Iraqi males. Results: Genotyping 90 male participants revealed a significantly higher frequency of the A allele and AA genotype among addicts, with the AA genotype increasing addiction risk up to 17-fold for alcohol and 14-fold for drug use. The GA genotype showed intermediate risk. Novelty: This is among the first studies to demonstrate a strong association between COMT rs4680 variants and addiction in the Iraqi population, highlighting allele-dose effects on susceptibility. Implications: These findings suggest that COMT polymorphism may serve as a potential biomarker for addiction vulnerability and provide a foundation for future genetic and pharmacological interventions in personalized addiction treatment.Highlight : COMT rs4680 polymorphism showed a strong association with the risk of drug and alcohol addiction, especially in the A (Met) allele and AA genotype. Individuals with the AA genotype had a 14-17 times greater risk of addiction than the control group. The GA genotype showed an intermediate risk, particularly in alcohol addiction (OR = 5.4) although it was not significant for drugs. Keywords : COMT, rs4680, Addiction, Val158Met, Dopamine